POLICY IMPLEMENTATION OF WORKING CULTURE DEVELOPMENT IN MINISTRY OF RELIGIOUS AFFAIRS - Munawwaroh, Salma; Larasati, Endang; Suwitri, Sri; Warsono, Hardi (Journal of process management and new technologies, 2019)
Indonesia as a religious state has the Ministry of Religious Affairs who has a vision and mission in realizing the Indonesian communities are obedient, harmonious, intellectually intelligent, emotional and spiritual as well as prosperous born inner. However, ironically, the ministry that should be the front guard of this morality, in 2012 was the ministry with the lowest perception index version of Corruption Eradication Commission known as KPK, and in 2014 the only ministry with the value of self under the standard of Corruption Eradication Commission known as KPK. Ministry of Administrative and Bureaucratic Reform has published a regulation No. 39 in 2012 on the guidelines for the development of work culture for ministries and institutions in 2012. This research aims to identify and analyze the policy implementation of working culture development of based on regulation Number 39 in 2012 in the Ministry of Religious Affairs and identify factors affecting the implementation of development policy of The Ministry of Religious Affairs. This research is a qualitative study using descriptive analytical techniques. The findings in this study, the Ministry of Religious Affairs have not developed a structured, comprehensive and sustainable work culture.